Turning waste into collective value: circular economy, informal labour, and community governance in Indonesian urban settlements - Fuad Rahman (Indonesian Journal of Applied Community Research, 2026)
Background: Surabaya generated 660,946.82 tons of waste in 2024, with households contributing 85.2% of the waste stream, making neighbourhood-based circular waste governance a pressing community development issue. Objective: This community engagement program aimed to strengthen circular economy literacy, household sorting practice, waste-bank documentation, and participatory governance among 40 eligible residents, waste-bank actors, and local partners in Kelurahan Rangkah, Kecamatan Tambaksari. Method: The method combined planning, implementation, and monitoring-evaluation through coordination meetings, needs assessment, training, mentoring, pre-post questionnaires, observation checklists, practice-output rubrics, waste-bank transaction logs, FGD guides, and follow-up indicators. Results: Planning produced three coordination meetings, 40 targeted needs-assessment responses, six mapped stakeholder groups, five evaluation instruments, and an eight-week mentoring schedule. Implementation consisted of one orientation, four training sessions, eight weeks of mentoring, two peer discussion forums, 85% attendance, 26 active mentoring participants, and 28 documented practice outputs. Implication: Monitoring-evaluation recorded 70% acceptable outputs, a mean capacity score movement from 52.0 to 73.2, two validation forums, one institutional follow-up plan, and a 3–6 month sustainability monitoring design. Novelty: The novelty of this program lies in integrating practical waste intervention, informal labour recognition, participatory data, simple quantitative evaluation, and institutional follow-up into one evidence-based community engagement model.